Analisis Pembiasaan Pendidikan Karakter Islami di MI Pembangunan Desa Tanggulrejo - Muslimin, Fatkhul; Zamzam, Alif Firdaus (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
The With the increase in modern knowledge, technology, and information, Indonesia faces many challenges. If the foundation of principles and strong moral standards is not upheld, then the character of the nation's children will deteriorate. The implementation of religious character education through habituation is very important to develop a character with noble character. The purpose of this study is to describe and analyze the implementation and supporting and inhibiting factors of religious character education through habituation in schools. This research is a qualitative descriptive research with the research subjects being school principals, teachers, and students. The data collection techniques in this study are observation, interviews, and documentation. The results of the study show that religion-based character education through habituation responds to the evaluation of daily habituation activities, voluntary habituation, exemplary habituation, and religious indicators of attitude and activity development. In addition, there are factors that support implementation such as teacher support, parent cooperation, and school facilities. The inhibiting factors include the child's own will and lack of support and recognition from their parents, teachers, and classmates.